Pengaruh Proses Blanching pada Pembuatan Tepung Terhadap Organoleptik Tepung Daun Pepaya Jepang (Cnidoscolus aconitifolius) - Abdul Hairuddin Angkat; Katherine Angeline Tambunan; Wanda Lestari (Lembaga Pengembangan Kinerja Dosen, 2024)
Japanese pepaya leaves have many benefits in the body, especially preventing anemia. Making Japanese pepaya leaf flour can encourage the emergence of various and practical processed products. One physical method for modifying flour is blanching. The aim of this research was to determine the effect of blanching on the organoleptic properties of Japanese pepaya leaf flour. This research was experimental with Randomized Control Design (RCD), with 3 treatments, namely making flour without blanching, making flour with water blanching and making flour with steam blanching and 2 repetitions. Data were collected using organoleptic tests which included color, taste and aroma of Japanese pepaya leaf flour by 20 panelists. The organoleptic test results showed that the most preferred color of Japanese pepaya leaf flour was treatment A with a value of (4.05) and p=0.00. In terms of aroma, treatment C was the most liked with a value of (4.1), p value = 0.00. Based on the taste of treatment C, it was liked with a value of (4.15) in the very, very like category and p = 0.00.